Penyuluhan Meminimalkan Residu Pestisida pada Bahan Pangan di MTs Lempur Kecamatan Gunung Raya Kabupaten Kerinci - Firna Varina; Asaibani Asaibani; Epit Erwandri (Asosiasi Dosen Pengabdian kepada Masyarakat Indonesia, 2022)
Farmers in their daily farming activities cannot be separated from the use of chemicals, especially fertilizers and pesticides. From an early age, it is necessary to seek an understanding of farmer children about the safe use of chemicals in their use and the impact of these chemicals on the safety of the agricultural products (vegetables and fruit). The purpose of this activity is to provide knowledge and awareness about how to minimize pesticide residues on vegetables and fruit so that these agricultural products are safe for family consumption for students at MTs Lempur, Gunung Raya District, Kerinci Regency, Jambi. The method used is face-to-face counseling by providing literature of material and conducting questions and answers deepening the material as well as quizzes with prizes at the end of the session. Community service activities regarding counseling on how to minimize pesticide residues in food, vegetables and fruit have been carried out well, and have received enthusiastic responses from students at MTs Lempur, Gunung Raya District, Kerinci Regency.